Acrocomia aculeata associated with doxorubicin: cardioprotection and anticancer activity - Monteiro-Alfredo, Tamaeh; dos Santos, Jéssica Maurino; Antunes, Kátia Ávila; Cunha, Janielle; da Silva Baldivia, Debora; Pires, Ana Salomé; Marques, Inês; Abrantes, Ana Margarida; Botelho, Maria Filomena; Monteiro, Lúcia; Gonçalves, Ana Cristina; Botelho, Wellington Henrique; et al. (Frontiers in Pharmacology, 2023)
Doxorubicin (Dox) is a chemotherapeutic agent widely used in the clinic, whose side effects include cardiotoxicity, associated with decreased antioxidant defenses and increased oxidative stress. The association of Dox with natural antioxidants can extend its use if not interfering with its pharmacological potential. In this study, we aimed to understand the effects and mechanisms of the aqueous extract of Acrocomia aculeata leaves (EA-Aa) in cancer cells and the co-treatment with Dox, in vitro and in vivo models. It was found that EA-Aa showed a relevant decrease in the viability of cancer cells (K562 and MCF-7) and increased apoptosis and death. The Dox cytotoxic effect in cotreatment with EA-Aa was increased in cancer cells. The therapeutic association also promoted a change in cell death, leading to a higher rate of apoptosis compared to the Dox group, which induced necrosis. In addition, in non-cancer cells, EA-Aa enhanced red blood cell (RBC) redox state with lower hemolysis and malondialdehyde (MDA) content and had no in vitro nor in vivo toxicity. Furthermore, EA-Aa showed antioxidant protection against Dox-induced cytotoxicity in H9c2 cells (cardiomyoblast), partially mediated by the NRF2 pathway. In vivo, EA-Aa treatment showed a relevant decrease in MDA levels in the heart, kidney, and brain, evaluated in C57Bl/6 mice induced to cardiotoxicity by Dox. Together, our results proved the effectiveness of EA-Aa in potentiating Dox anticancer effects, with antioxidant and cardioprotective activity, suggesting EA-Aa as a potential Dox pharmacological adjuvant.